PRODUKTIVITAS SERASAH Rhizophora apiculata Blume danAvicennia marina (Forsk.) Vierh. DI HUTAN MANGROVE KELURAHAN UNTIA, KOTA MAKASSAR - Muhammad Ruslan Umar; Ainun Saputri (BIOMA : JURNAL BIOLOGI MAKASSAR, 2025)
The role of mangrove forests as a home for aquatic biota is insepar-able from their function as producers of litter such as leaf litter, flowers, twigs and fruits, which can be converted into nutrients. These nutrients are reabsorbed by mangrove plants for growth and partially utilized by other organisms in the water.  This study aims to analyze the productivity of mangrove litter Rhizophora   apiculata Blume and Avicennia marina(Forsk.) Vierhin supporting water fertility in Untia Village, Makassar City. The research method was conducted with non-destructive vegetation analysis using litter traps, conducted in R. apiculata area (Station I) and A. marina area (Station II), and each consists of 3 sampling points. Litter was collected every other day for a period of two months. The average daily litter productivity of A. marina was highest at sampling site III with 7.06 grams/m2/day, while for R. apiculata it was 2.93 grams/m2/day at sampling site II. In general, the average daily productivity of Avicennia marina litter was 5.45 grams/m2/day, higher than the average daily productivity of Rhizophora apiculata litter, which was 2.76 grams/m2/day. A. marina litter produc-tivity reached an average of 19.89 tons/ha/year, while R. apiculata litter productivity reached an average of 10.09 tons/ha/year. The productivity of the mangrove forest litter in the urban village of Untia is classified as a good criterion for supporting water fertility. Keywords: productivity, litter, Rhizophora apiculata,Avicennia marina